Modified porous silica negative electrode material of lithium ion battery as well as preparation method and application of modified porous silica negative electrode material
By constructing porous defects on the surface of silicon oxide and growing carbon nanotubes and nitrogen-doped conductive coating and repairing carbon layers in situ, a modified porous silicon oxygen negative electrode material was prepared, which solved the problems of large volume changes and poor conductivity of silicon oxygen negative electrode material, and achieved efficient and stable lithium-ion battery performance.
Patent Information
- Application Number
- CN202411893011.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing silicon oxygen negative electrode materials have large volume changes and poor conductivity, resulting in unstable material structure, low battery efficiency and poor circulation ratio.
Modified porous silicon oxygen negative electrode material was prepared by constructing porous defects on the surface of silicon oxide and growing carbon nanotubes and nitrogen-doped conductive coatings and repairing carbon layers in situ. The material includes a core layer and a shell layer, the core layer is a premagnesium silicon oxygen material, and the shell layer is a carbon nanotube and a repair carbon layer.
The modified porous silicon oxygen negative electrode material has good electronic conductivity and ionic conductivity, which can effectively alleviate volume expansion and improve the first-term effect, conductivity and cycle rate performance of the battery.
Smart Images

Figure CN119674020A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a lithium ion battery modified porous silicon oxygen negative electrode material and a preparation method and application thereof. Background Art
[0002] As lithium-ion batteries pursue high energy density, high rate performance, and high safety performance, the low specific capacity (theoretical capacity is 372 mAh / g) of graphite anode materials limits their further development. Silicon-based materials have attracted widespread attention due to their high theoretical specific capacity. Si forms Li at room temperature. 15 Si4, the corresponding specific capacity of 3579mAh / g is much higher than that of graphite negative electrode. However, during the lithiation / delithiation process, Si negative electrode materials will have problems such as volume expansion (~300%), unstable SEI film and poor conductivity, which affect their application in lithium-ion batteries. SiO has better commercial prospects than pure silicon negative electrode because of its high theoretical capacity (2680mAh / g), low lithium insertion and extraction potential and small volume expansion (~150%). However, since SiO will irreversibly form L2O and lithium silicate in the first cycle, the initial Coulomb efficiency of SiO is relatively low, and SiO also has disadvantages such as low intrinsic conductivity, poor chemical activity, and poor cycle rate performance.
[0003] Pre-magnesium technology usually uses magnesium thermal reduction reaction to improve the first coulombic efficiency of SiO. However, magnesium thermal reaction is usually violent, and excessive local temperature will cause the size of silicon crystals to increase sharply, and magnesium oxide will also agglomerate into larger particles, affecting the cycle performance of the battery. Chinese patent CN110993900A discloses a method for preparing a magnesium silicate-carbon-coated silicon oxide composite negative electrode material, weighing a certain mass ratio of Mg powder, MgO powder and carbon-coated silicon oxide powder, metal chloride, sintering under the protection of inert gas, washing with water to remove the chloride layer, and drying to obtain a magnesium silicate-carbon-coated silicon oxide composite negative electrode material, but the conductivity and cycle rate performance of the material are poor. Therefore, it is necessary to structurally design SiO so that it can maintain a stable structure and a thinner SEI film during use, and obtain good conductivity, high coulombic efficiency, excellent cycle rate performance, etc. Summary of the invention
[0004] In order to solve the problems of large volume change and poor conductivity of existing silicon-oxygen negative electrode materials, resulting in unstable material structure, low battery initial efficiency and poor cycle rate, the present invention provides a lithium-ion battery modified porous silicon-oxygen negative electrode material and a preparation method thereof. The silicon-oxygen negative electrode material has good electronic conductivity and ionic conductivity, is conducive to the rapid deintercalation of lithium ions, and has a stable structure, can effectively alleviate volume expansion, and the prepared material has a high initial efficiency, excellent conductivity and cycle rate performance.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A modified porous silicon oxide negative electrode material for a lithium ion battery comprises an inner core layer and an outer shell layer, wherein the inner core layer is a pre-magnesiumized silicon oxide material, and the outer shell layer is coated on the pre-magnesiumized silicon oxide material, wherein the inner core layer pre-magnesiumized silicon oxide material is porous SiO, comprising Si particles, SiO2 particles and magnesium silicate; the outer shell layer is carbon nanotubes in-situ grown on the surface of the porous SiO, and a carbon nanotube-nitrogen doped conductive coating and a repaired carbon layer; and the porous SiO pores are embedded with carbon nanotubes.
[0007] The present invention also provides a method for preparing the modified porous silicon oxide negative electrode material for lithium ion batteries, which forms porous defects on the surface of silicon oxide by pre-magnesiation, modifies the active sites of grafting reaction, in-situ grows carbon nanotubes on the sites where the catalyst is attached to the surface of porous silicon oxide, introduces an organic carbon source and a nitrogen source to form a nitrogen-doped conductive coating layer and repairs the carbon layer. Specifically, the following steps are included:
[0008] S1, after mixing SiO2 with a magnesium source and a pore-forming agent, heating to a certain temperature in an argon atmosphere, keeping the temperature to react, and acid-washing, water-washing and drying the product to obtain porous SiO2;
[0009] S2, stirring the porous SiO2 obtained in S1, a modifier and a catalyst in a solvent, and drying to obtain modified porous SiO2;
[0010] S3, the modified SiO obtained in S2 is mixed with a carbon source, heated to a certain temperature in an argon atmosphere, and kept warm for in-situ carbon tube growth, and then the carbon source gas and nitrogen source gas are directly introduced to carry out carbon layer coating and repair reaction at a certain temperature, and the modified porous silicon oxygen negative electrode material is obtained after cooling.
[0011] Preferably, D of the SiO raw material S1 is 50 =5μm; the magnesium source is one or more of magnesium powder, magnesium hydride, magnesium oxide, magnesium silicide, magnesium carbonate, magnesium chloride, magnesium sulfate, magnesium nitrate and magnesium silicate; the pore-forming agent is one or more of sodium chloride, sodium citrate, sodium carbonate, ammonium bicarbonate, zinc chloride, potassium chloride and calcium chloride; the mass ratio of SiO to magnesium source and pore-forming agent is 1:(0.1-1):(0.2-2).
[0012] Preferably, in S1, the temperature is heated to 550-950° C. in an argon atmosphere and kept warm for 2-8 hours. The pickling is carried out using one or more of hydrochloric acid, sulfuric acid, nitric acid and acetic acid, and the acid concentration is 0.1-4 mol / L.
[0013] Preferably, the modifier in S2 is hexadecyltrimethylammonium bromide, hexadecyltriethylammonium bromide, polyvinylpyrrolidone (molecular weight 58000), γ-aminopropyltriethoxysilane, octavinylsilsesquioxane, oleic acid, etc.; the catalyst is one or more of ferric nitrate nonahydrate, ferrocene, nickel nitrate hexahydrate, zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and manganese chloride tetrahydrate; the mass ratio of the porous SiO, the modifier and the catalyst is (10-20):(0.5-2):1; the solvent is one or more of water, ethanol, methanol, formaldehyde, acetone, dimethyl sulfoxide, and N-methylpyrrolidone.
[0014] Preferably, the carbon source in S3 is one or more of melamine, cyanuric acid, phenolic resin, urea, resorcinol, dopamine hydrochloride, glucose, chitosan, polyaniline, polyacrylonitrile, imidazoles, and pyridines, and the mass ratio of the modified porous SiO to the carbon source is (5-20):1.
[0015] Preferably, the heating rate in S3 is continued to be increased to 550-750°C at 1-10°C / min, and kept at this temperature for 2-6h; then the temperature is continued to be increased to 650-850°C at 2-6°C / min, and the carbon source gas and nitrogen source gas are introduced at this temperature and kept for 10-120min.
[0016] Preferably, the carbon source gas in S3 can be one or more of acetylene, ethylene, methane, ethane, propane and n-butane; the nitrogen source gas is nitrogen or ammonia, and the volume ratio of the carbon source gas, nitrogen source gas and argon is 1:(0.1~1):(1~10).
[0017] The present invention also provides the application of the modified porous silicon oxide negative electrode material of lithium ion battery in lithium ion battery. The prepared modified porous silicon oxide negative electrode material, conductive agent (Super P), binder CMC and SBR (mass ratio 6:4) are mixed into slurry at a mass ratio of 8:1:1, applied to a copper foil current collector, and vacuum dried for 12 hours to form a negative electrode sheet; a lithium sheet is used as a counter electrode, Celgard 2500 is used as a diaphragm, 1 mol / L LiPF6 (solvent is a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) is used as an electrolyte, 1% VC and 5% fluoroethylene carbonate (FEC) are added to the electrolyte, and a CR2025 button battery is assembled in a glove box. The assembled battery was left at rest at 25°C for 10 hours, and constant current charge and discharge tests were performed on the Wuhan Blue Electric electrochemical test channel, with a current density of 0.1C (1C = 1000mAh / g), a charge cut-off voltage of 2.00V, and a discharge cut-off voltage of 0.005V. The performance test of the assembled battery showed that the first coulomb efficiency was 83.87%, and the 50-cycle capacity retention rate reached 94.50%.
[0018] Compared with the prior art, the present invention has the following beneficial effects: a modified porous silicon oxygen negative electrode material is prepared by constructing porous defects on the surface of silicon oxide, modifying in-situ catalytic growth of carbon nanotubes and doping, coating and repairing structures. The modified porous silicon oxygen negative electrode material of the present invention includes an inner core layer and an outer shell layer coated on the inner core layer, the inner core layer is a pre-magnesiumized silicon oxygen material, i.e., porous SiO; the outer shell layer is carbon nanotubes grown in situ on the surface of porous SiO, and carbon nanotube-nitrogen doped conductive coating and repaired carbon layer, and the porous SiO pores are embedded with carbon nanotubes. This method is conducive to the rapid and uniform growth of carbon nanotubes on the surface and in the pores of porous silicon oxygen powder, forming a firmly connected structure between the inner core layer and the outer shell layer; at the same time, the "point-line-point" connection method improves the electronic conductivity and ionic conductivity of the material. The modified porous silicon oxygen negative electrode material for lithium ion batteries obtained in this way has a high first efficiency, excellent conductivity and cycle rate performance. The modified porous silicon oxygen negative electrode material provided by the present invention can be used as a negative electrode active material for lithium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments and comparative examples of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is the SEM image of the material obtained in Example 1 of the present invention.
[0021] Figure 2 This is the SEM image of the material obtained in Comparative Example 3 of the present invention.
[0022] Figure 3 This is the XRD diagram of the material obtained in Comparative Example 3 of the present invention.
[0023] Figure 4 This is the charge and discharge curve of the material obtained in Example 1 of the present invention.
[0024] Figure 5 This is a cycle performance diagram of the material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to further illustrate the present invention, the modified porous silicon-oxygen negative electrode material for lithium-ion batteries and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments.
[0026] Example 1
[0027] The preparation method of the modified porous silicon oxide negative electrode material for lithium ion batteries in this embodiment is as follows:
[0028] S1. Weigh 10 g SiO powder (D 50 =5μm), 2.5gMg powder, 2.5gNaCl, put into a degassing machine for high energy mixing, then put into a tube furnace, pass argon (200mL / min), raise the temperature from room temperature to 650℃ at 5℃ / min, and keep it for 4h. After cooling, take it out, put it into 100mL (1mol / L) hydrochloric acid solution, stir for 4h, wash it with deionized water and ethanol alternately by centrifugation, and dry it in vacuum at 60℃ to obtain porous SiO;
[0029] S2, weighing 10g of the porous SiO2 obtained in S1, 1g of hexadecyltrimethylammonium bromide, 0.15g of ferric nitrate nonahydrate, and 0.35g of nickel nitrate hexahydrate, put them into 100mL of ethanol, stirred at 40°C for 1h, and dried at 60°C to obtain modified porous SiO2;
[0030] S3, weigh 5g of the modified porous SiO in S2 and 0.5g of melamine, mix them, put them into a ball mill at 250rpm for 2h, then put them into a CVD vapor deposition furnace, and heat them to 700℃ at 10℃ / min in an argon atmosphere (100mL / min), keep them warm for 30min, then directly heat them from 700℃ to 750℃ at 5℃ / min, then pass acetylene (20mL / min) and ammonia (10mL / min) and keep them warm for 30min. Cool down the furnace to obtain nitrogen-doped modified porous silicon oxygen negative electrode material.
[0031] Example 2
[0032] The preparation method of the modified porous silicon oxide negative electrode material for lithium ion batteries in this embodiment is as follows:
[0033] S1. Weigh 10 g SiO powder (D 50 =5μm), 2.5gMg, 10gZnCl, put into a degassing machine for high energy mixing, then put into a tube furnace, pass argon (200mL / min), raise the temperature from room temperature to 850℃ at 5℃ / min, and keep it for 4h. After cooling, take it out, put it into 100mL (1mol / L) hydrochloric acid solution, stir for 4h, wash it with deionized water and ethanol alternately by centrifugation, and dry it in vacuum at 60℃ to obtain porous SiO;
[0034] S2, weighing 10 g of the porous SiO2 obtained in S1, 1 g of hexadecyltrimethylammonium bromide, 0.15 g of ferric nitrate nonahydrate, and 0.35 g of nickel nitrate hexahydrate, put them into 100 mL of ethanol, stirred at 40°C for 1 h, and dried at 60°C to obtain a modified porous SiO2;
[0035] S3, weigh 5g of the modified porous SiO in S2 and 0.5g of melamine, mix them, put them into a ball mill at 250rpm for 2h, then put them into a CVD vapor deposition furnace, and heat them to 700℃ at 10℃ / min in an argon atmosphere (100mL / min), keep them warm for 30min, then directly heat them from 700℃ to 750℃ at 5℃ / min, then pass acetylene (20mL / min) and ammonia (10mL / min) and keep them warm for 30min. Cool down the furnace to obtain nitrogen-doped modified porous silicon oxygen negative electrode material.
[0036] Example 3
[0037] The preparation method of the modified porous silicon oxide negative electrode material for lithium ion batteries in this embodiment is as follows:
[0038] S1. Weigh 10g SiO powder (D50 = 5μm), 2.5g Mg, 2.5g NaCl, put them into a degassing machine for high-energy mixing, then put them into a tube furnace, pass argon (200mL / min), raise the temperature from room temperature to 850℃ at 5℃ / min, and keep it warm for 4h. After cooling, take it out, put it into 100mL (1mol / L) hydrochloric acid solution, stir it for 4h, wash it with deionized water and ethanol alternately by centrifugation, and dry it in vacuum at 60℃ to obtain porous SiO;
[0039] S2, weighing 10 g of the porous SiO2 obtained in S1, 1 g of polyvinyl pyrrolidone (molecular weight 58,000), and 0.15 g of ferric nitrate nonahydrate, put them into 100 mL of ethanol, stirred at 40°C for 1 h, and dried at 60°C to obtain a modified porous SiO2;
[0040] S3, weigh 5g of the modified porous SiO in S2 and 0.5g of melamine, mix them, put them into a ball mill at 250rpm for 2h, then put them into a CVD vapor deposition furnace, and heat them to 700℃ at 10℃ / min in an argon atmosphere (100mL / min), keep them warm for 30min, then directly heat them from 700℃ to 750℃ at 5℃ / min, then pass acetylene (20mL / min) and ammonia (10mL / min) and keep them warm for 30min. Cool down the furnace to obtain nitrogen-doped modified porous silicon oxygen negative electrode material.
[0041] Example 4
[0042] The preparation method of the modified porous silicon oxide negative electrode material for lithium ion batteries in this embodiment is as follows:
[0043] S1. Weigh 10 g SiO powder (D 50=5μm), 2.5gMg powder, 2.5gNaCl, put into a degassing machine for high energy mixing, then put into a tube furnace, pass argon (200mL / min), raise the temperature from room temperature to 650℃ at 5℃ / min, and keep it for 4h. After cooling, take it out, put it into 100mL (1mol / L) hydrochloric acid solution, stir for 4h, wash it with deionized water and ethanol alternately by centrifugation, and dry it in vacuum at 60℃ to obtain porous SiO;
[0044] S2, weighing 10 g of the porous SiO2 obtained in S1, 1 g of hexadecyltrimethylammonium bromide, 0.15 g of ferric nitrate nonahydrate, and 0.35 g of nickel nitrate hexahydrate, put them into 100 mL of ethanol, stirred at 40°C for 1 h, and dried at 60°C to obtain a modified porous SiO2;
[0045] S3, weigh 5g of the modified porous SiO in S2 and 0.5g of phenolic resin, mix them, put them into a ball mill at 250rpm for 2h, then put them into a CVD vapor deposition furnace, and heat them to 700℃ at 10℃ / min under argon atmosphere (100mL / min), keep them warm for 30min, then directly heat them from 700℃ to 750℃ at 5℃ / min, then pass acetylene (20mL / min) and ammonia (10mL / min) and keep them warm for 30min. Cool down the furnace to obtain nitrogen-doped modified porous silicon oxygen negative electrode material.
[0046] Comparative Example 1
[0047] Compared with Example 1, no pore-forming agent is added, and the specific steps are as follows:
[0048] S1. Weigh 10g SiO powder (D50 = 5μm) and 2.5g Mg powder, put them into a degassing machine for high-energy mixing, then put them into a tube furnace, pass argon (200mL / min), increase the temperature from room temperature to 650℃ at 5℃ / min, and keep it warm for 4h. After cooling, take it out, put it into 100mL (1mol / L) hydrochloric acid solution, stir for 4h, wash it with deionized water and ethanol alternately by centrifugation, and dry it in vacuum at 60℃ to obtain pre-magnesiumized SiO;
[0049] S2, weigh 10g of the pre-magnesiumized SiO2 obtained in S1, 1g of hexadecyltrimethylammonium bromide, 0.15g of ferric nitrate nonahydrate, and 0.35g of nickel nitrate hexahydrate, put them into 100mL of ethanol, stir at 40°C for 1h, and dry at 60°C to obtain modified pre-magnesiumized SiO2;
[0050] S3, weigh 5g of the modified porous SiO in S2 and 0.5g of melamine, mix them, put them into a ball mill at 250rpm for 2h, then put them into a CVD vapor deposition furnace, and heat them to 700℃ at 10℃ / min in an argon atmosphere (100mL / min), keep them warm for 30min, then directly heat them from 700℃ to 750℃ at 5℃ / min, then pass acetylene (20mL / min) and ammonia (10mL / min) and keep them warm for 30min. Cool down the furnace to obtain nitrogen-doped modified porous silicon oxygen negative electrode material.
[0051] Comparative Example 2
[0052] Compared with Example 1, no pre-magnesiation reaction was performed, and the specific steps were as follows:
[0053] S1. Weigh 10 g SiO powder (D50 = 5 μm) and 1 g hexadecyltrimethylammonium bromide, 0.15 g ferric nitrate nonahydrate, and 0.35 g nickel nitrate hexahydrate, put them into 100 mL ethanol, stir at 40 ° C for 1 h, and dry at 60 ° C to obtain modified SiO;
[0054] S2, weigh 5g of modified SiO in S2 and 0.5g of melamine, mix them, put them into a ball mill at 250rpm for 2h, then put them into a CVD vapor deposition furnace, and heat them to 700℃ at 10℃ / min in an argon atmosphere (100mL / min), keep them warm for 30min, then directly heat them from 700℃ to 750℃ at 5℃ / min, then pass acetylene (20mL / min) and ammonia (10mL / min) and keep them warm for 30min. Cool down the furnace to obtain nitrogen-doped modified porous silicon oxygen negative electrode material.
[0055] Comparative Example 3
[0056] Compared with Example 1, the carbon nanotubes are grown in situ without modification, catalyst or carbon source, and the specific steps are as follows:
[0057] S1. Weigh 10 g SiO powder (D 50 =5μm), 2.5gMg powder, 2.5gNaCl, put into a degassing machine for high energy mixing, then put into a tube furnace, pass argon (200mL / min), raise the temperature from room temperature to 650℃ at 5℃ / min, and keep it for 4h. After cooling, take it out, put it into 100mL (1mol / L) hydrochloric acid solution, stir for 4h, wash it with deionized water and ethanol alternately by centrifugation, and dry it in vacuum at 60℃ to obtain porous SiO;
[0058] S2, weigh 5g of the porous SiO in S1 and put it into a CVD vapor deposition furnace, and heat it to 700°C at 10°C / min in an argon atmosphere (100mL / min), keep it warm for 30min, and then directly heat it from 700°C to 750°C at 5°C / min, and then introduce acetylene (20mL / min) and ammonia (10mL / min) and keep it warm for 30min. Then cool it down in the furnace to obtain nitrogen-doped porous silicon oxygen negative electrode material.
[0059] Comparative Example 4
[0060] Compared with Example 1, the nitrogen-doped amorphous carbon layer coating and repairing are not performed, and the specific steps are as follows:
[0061] S1. Weigh 10 g SiO powder (D 50 =5μm), 2.5gMg powder, 2.5gNaCl, put into a degassing machine for high energy mixing, then put into a tube furnace, pass argon (200mL / min), raise the temperature from room temperature to 650℃ at 5℃ / min, and keep it for 4h. After cooling, take it out, put it into 100mL (1mol / L) hydrochloric acid solution, stir for 4h, wash it with deionized water and ethanol alternately by centrifugation, and dry it in vacuum at 60℃ to obtain porous SiO;
[0062] S2, weighing 10 g of the porous SiO2 obtained in S1, 1 g of hexadecyltrimethylammonium bromide, 0.15 g of ferric nitrate nonahydrate, and 0.35 g of nickel nitrate hexahydrate, put them into 100 mL of ethanol, stirred at 40°C for 1 h, and dried at 60°C to obtain a modified porous SiO2;
[0063] S3, weigh 5g of the modified porous SiO in S2 and 0.5g of melamine, mix them, put them into a ball mill at 250rpm for 2h, then put them into a CVD vapor deposition furnace, and heat them to 700℃ at 10℃ / min in an argon atmosphere (100mL / min), and keep them warm for 30min. Then cool them down in the furnace to obtain a porous silicon-oxygen negative electrode material.
[0064] The SiO raw material and the negative electrode active materials prepared in the above embodiments and comparative examples were prepared into negative electrode sheets for batteries, which were assembled into batteries for various performance tests. The test results are shown in Table 1.
[0065] Table 1. Electrochemical properties of SiO raw materials, modified porous silicon oxide negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-4.
[0066]
[0067] As can be seen from Table 1, in Comparative Example 1, no pore-forming agent is added, and the pre-magnesium reaction rate is too fast, and a loose porous defect structure cannot be effectively formed on the surface of the SiO particles, which is not conducive to the transmission of lithium ions and electrons. The material has a low initial efficiency and poor cycle stability. In Comparative Example 2, no pre-magnesiumization reaction is performed, and the initial efficiency of the material is low. The material has poor mechanical strength and structural stability, cannot effectively resist the stress in the lithiation state, and expands severely. In Comparative Example 3, porous silicon is not modified and a catalyst is added to in situ grow carbon nanotubes. The material has poor conductivity and poor cycle rate performance. In Comparative Example 4, no nitrogen-doped amorphous carbon layer coating and repair layer are performed, and the solid-liquid interface between the electrode material and the electrolyte is unstable, and the cycle performance is poor. The present invention prepares a modified porous silicon-oxygen negative electrode material by constructing porous defects on the surface of silicon oxide, modifying in-situ catalytic growth of carbon nanotubes and doping and coating repair structures, which is conducive to the rapid and uniform growth of carbon nanotubes on the surface of porous silicon-oxygen powder and in the pores, forming a firm connection structure between the inner core layer and the outer shell layer; at the same time, the "point-line-point" connection method improves the electronic conductivity and ionic conductivity of the material. The modified porous silicon-oxygen negative electrode material for lithium-ion batteries obtained in this way has a high first efficiency, excellent conductivity and cycle rate performance.
[0068] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A lithium-ion battery modified porous silicon oxygen negative electrode material, characterized in that: The invention comprises an inner core layer and an outer shell layer, wherein the inner core layer is a pre-magnesiumized silicon-oxygen material, and the outer shell layer is coated on the pre-magnesiumized silicon-oxygen material, and the pre-magnesiumized silicon-oxygen material of the inner core layer is porous SiO; the outer shell layer is carbon nanotubes in-situ grown on the surface of the porous SiO, and carbon nanotube-nitrogen-doped conductive coating and repaired carbon layer; and carbon nanotubes are embedded in the porous SiO channels.
2. The method for preparing a lithium-ion battery modified porous silicon oxide negative electrode material according to claim 1, characterized in that: The following steps are included: S1, after mixing SiO2 with a magnesium source and a pore-forming agent, heating to a certain temperature in an argon atmosphere, keeping the temperature to react, and acid-washing, water-washing and drying the product to obtain porous SiO2; S2, stirring the porous SiO2 obtained in S1, a modifier and a catalyst in a solvent, and drying to obtain modified porous SiO2; S3, mixing the modified porous SiO2 obtained in S2 with a carbon source, heating to a certain temperature in an argon atmosphere, keeping the temperature to perform in-situ carbon tube growth, and then directly introducing carbon source gas and nitrogen source gas to perform carbon layer coating and repair reaction at a certain temperature, and obtaining a modified porous silicon oxygen negative electrode material after cooling.
3. The method for preparing the modified porous silicon-oxygen negative electrode material for lithium-ion batteries according to claim 2, characterized in that In S1, the magnesium source is one or more of magnesium powder, magnesium hydride, magnesium oxide, magnesium silicide, magnesium carbonate, magnesium chloride, magnesium sulfate, magnesium nitrate and magnesium silicate; the pore-forming agent is one or more of sodium chloride, sodium citrate, sodium carbonate, ammonium bicarbonate, zinc chloride, potassium chloride and calcium chloride; the mass ratio of SiO to magnesium source and pore-forming agent is 1:(0.1~1):(0.2~2).
4. The method for preparing a lithium ion battery modified porous silicon oxygen negative electrode material according to claim 2, characterized in that In S1, heat to 550~950℃ in argon atmosphere and keep warm for 2~8h.
5. The method for preparing the modified porous silicon-oxygen negative electrode material for lithium-ion batteries according to claim 2, characterized in that In S1, pickling uses one or more of hydrochloric acid, sulfuric acid, nitric acid, and acetic acid; the acid concentration is 0.1~4mol / L.
6. The method for preparing a lithium-ion battery modified porous silicon oxide negative electrode material according to claim 2, characterized in that: The modifier in S2 is one or more of hexadecyltrimethylammonium bromide, hexadecyltriethylammonium bromide, polyvinylpyrrolidone, γ-aminopropyltriethoxysilane, octavinylsilsesquioxane, and oleic acid; the catalyst is one or more of ferric nitrate nonahydrate, ferrocene, nickel nitrate hexahydrate, zinc nitrate hexahydrate, cobalt nitrate hexahydrate, and manganese chloride tetrahydrate; the solvent is one or more of water, ethanol, methanol, formaldehyde, acetone, dimethyl sulfoxide, and N-methylpyrrolidone; the mass ratio of the porous SiO, the modifier, and the catalyst is (10~20):(0.5~2):
1.
7. The method for preparing a lithium-ion battery modified porous silicon oxide negative electrode material according to claim 2, characterized in that: The carbon source in S3 is one or more of melamine, cyanuric acid, phenolic resin, urea, resorcinol, dopamine hydrochloride, glucose, chitosan, polyaniline, polyacrylonitrile, imidazoles, and pyridines; the mass ratio of modified porous SiO to the carbon source is (5-20):
1.
8. The method for preparing a lithium-ion battery modified porous silicon oxide negative electrode material according to claim 2, characterized in that: The heating rate in S3 is continued to be 1-10°C / min to 550-750°C, and the temperature is kept at this temperature for 2-6 hours; then the temperature is continued to be raised to 650-850°C at 2-6°C / min, and the carbon source gas and the nitrogen source gas are introduced at this temperature and kept at this temperature for 10-120 minutes.
9. The method for preparing a lithium-ion battery modified porous silicon oxide negative electrode material according to claim 2, characterized in that: The carbon source gas in S3 is one or more of acetylene, ethylene, methane, ethane, propane and n-butane; the nitrogen source gas is nitrogen or ammonia, and the volume ratio of the carbon source gas, the nitrogen source gas and the argon gas is 1:(0.1~1):(1~10).
10. The use of the modified porous silicon oxide negative electrode material for lithium ion batteries according to claim 1 as a negative electrode material for lithium ion batteries, characterized in that: The assembled battery was performance tested under the conditions of current density of 0.1C, charge cut-off voltage of 2.00V and discharge cut-off voltage of 0.005V. The first coulombic efficiency was 83.87% and the capacity retention rate after 50 cycles reached 94.50%.
Citation Information
Patent Citations
Magnesium silicate-carbon coated silicon monoxide composite negative electrode material and preparation method thereof
CN110993900A
Cited By
Zinc-dichloroimidazole coordination dense membrane and preparation method thereof
CN120630591A